Penerapan Evidence Based Practice Nursing ( EBPN ) Elevasi Kaki terhadap Penurunan Foot Edema pada Pasien Congestive Heart Failure (CHF) - Elidia Dewi; Wati Jumiati; Melati Fajarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
failure (CHF) based on the results of Evidence-Based Practice Nursing (EBPN) research. The design used is using a case study. Case studies in this innovative design are case studies by applying research results in the form of providing leg elevation to reduce edema in CHF patients with leg edema at Tarakan Hospital. Doing foot elevation three times daily for two days can reduce leg edema in CHF patients. From the interventions carried out on the three patients, data were obtained on decreased edema in foot edema. Keywords: Elevation of the Feet, Edema, Congestive Heart Failure (CHF)